Chelated Nitrogen-Sulphur-Codoped TiO2: Synthesis, Characterization, Mechanistic, and UV/Visible Photocatalytic Studies - Hayat Khan; Imran Khan Swati; Mohammad Younas; Asmat Ullah (International Journal of Photoenergy)
This study presents in detail the physicochemical, photoluminescent, and photocatalytic properties of carboxylic acid chelated nitrogen-sulphur-codoped TiO2. From the Fourier transform infrared spectroscopic study, it was revealed that the formate group formed bidentate bridging linkage while the acetate group coordinated in a bidentate chelating mode with a titanium precursor. In compliance with X-ray diffraction data, the anatase to rutile transformation temperature was extended due to carboxylic acid chelation and NS codoping. Raman analysis indicated four Raman peaks at 146, 392, 512, and 632 cm−1 for the precalcined chelated TiO2; on incorporation with NS dopants, an increase in Raman intensity for these peaks was recorded, indicating the structure stability of the anatase phase. Furthermore, X-ray photoelectron spectroscopic study revealed the presence of anionic doping of nitrogen and cationic doping of sulphur in the lattice of TiO2. When evaluating the UV-visible photodegradation rate of 4-chlorophenol, the modified TiO2 (NS0.06-TFA) showed the highest photocatalytic activity. In connection with the activity tests, several scavenger agents were employed to elucidate the significance of the different reactive oxidizing species during the photocatalytic process. Moreover, the transfer pathways of photogenerated carriers and the photocatalytic reaction mechanism of modified TiO2 were also explained in detail.